2012
DOI: 10.1016/j.str.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Protein KpOmpA Anchoring the Outer Membrane of Klebsiella pneumoniae Unfolds and Refolds in Response to Tensile Load

Abstract: In Klebsiella pneumoniae the transmembrane β-barrel forming outer membrane protein KpOmpA mediates adhesion to a wide range of immune effector cells, thereby promoting respiratory tract and urinary infections. As major transmembrane protein OmpA stabilizes Gram-negative bacteria by anchoring their outer membrane to the peptidoglycan layer. Adhesion, osmotic pressure, hydrodynamic flow, and structural deformation apply mechanical stress to the bacterium. This stress can generate tensile load to the peptidoglyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 50 publications
(88 reference statements)
4
46
0
Order By: Relevance
“…It was previously shown, that each force peak of this unfolding pattern describes an unfolding step and intermediate of OmpG 46,48,49 . It was also shown, that this pattern is specific for pulling the N-terminal end of OmpG, which faces the periplasmic space of E. coli 46,48,49 . The OMV membranes thus exposed their periplasmic surface to the buffer solution.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It was previously shown, that each force peak of this unfolding pattern describes an unfolding step and intermediate of OmpG 46,48,49 . It was also shown, that this pattern is specific for pulling the N-terminal end of OmpG, which faces the periplasmic space of E. coli 46,48,49 . The OMV membranes thus exposed their periplasmic surface to the buffer solution.…”
Section: Resultsmentioning
confidence: 92%
“…For each approach and retraction cycle a force-distance curve was recorded. In about 0.3‰ of attempts ( n  = 162,657), the force-distance curves showed the distinct saw-tooth like unfolding pattern of an Omp 46,48,49 . This indicated that the OmpG density in OMVs was sufficient to pick up single OmpG molecules for SMFS.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, because these interactions alter the physical properties of LacY (reviewed in ref. 9), the energetic, kinetic, and mechanical properties of LacY that fulfill different functional roles during transport remain to be characterized.Atomic force microscopy (AFM)-based single-molecule force spectroscopy (SMFS) has been applied to localize and quantify interactions that stabilize structural elements of an increasing number of native membrane proteins (20)(21)(22)(23)(24)(25). Because SMFS can be used with membrane proteins embedded in native or synthetic lipid membranes under physiological conditions, the method has been used to assess interactions that change upon substrate binding, insertion of mutations, and assembly or lipid composition of the membrane (26-35).…”
mentioning
confidence: 99%
“…Atomic force microscopy (AFM)-based single-molecule force spectroscopy (SMFS) has been applied to localize and quantify interactions that stabilize structural elements of an increasing number of native membrane proteins (20)(21)(22)(23)(24)(25). Because SMFS can be used with membrane proteins embedded in native or synthetic lipid membranes under physiological conditions, the method has been used to assess interactions that change upon substrate binding, insertion of mutations, and assembly or lipid composition of the membrane (26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
mentioning
confidence: 99%
“…(19). While the refolding pathway of chemically denatured OmpA protein appears to be best described by the concerted process, it is interesting to note that mechanical unfolding of the related protein KpOmpA from Klebsiella pneumoniae results in a stepwise unfolding process where individual β hairpins unfold successively [64]. Similar behavior has also been observed in β barrels OmpG and FhuA [65,66].…”
Section: Folding Pathways For β Barrelsmentioning
confidence: 70%